DATA MART DESIGN IN BKPP BANDUNG USING FROM ENTERPRISE MODELS TO DIMENSIONAL MODELS METHOD - Amalia Utami; Bayu Rimba Pratama; Septian Rheno Widianto (LPPM Nusa Mandiri, 2020)
The data warehouse is a single data storage that is complete and consistent with subject-oriented, integrated, non-volatile, and time-variant characteristics that can be used to support decisions. While Data mart is a subset of a data warehouse that supports the information needs of certain departments or business process functions. Badan Kepegawaian, Pendidikan Pelatihan (BKPP) of Bandung Municipality has a history of employee mutation transactions that have not been optimally utilized so it will be very useful if the data can be made into a data mart. This data mart development method uses the From Enterprise Models to Dimensional Models method as its design method and the Bottom-Up Approach as an approach in developing a data mart. This data mart developed using the PostgreSQL database and the PHP language. The purpose of this research is to develop human resource data mart by optimizing the utilization of historical data from employee mutation transactions. The results of this research are human resources data mart that accommodates historical data on employee mutation transactions and produces information that is useful for the Top Management to support the making decision.